2000
DOI: 10.1021/ma991496b
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Dynamic Light Scattering Study on the Dynamics of Silica Gels during Gelation Process

Abstract: The dynamics and structure have been compared for two types of silica gels prepared from tetramethoxysilane in dimethylformamide under acidic and basic conditions. An in-situ time-resolved dynamic light scattering (TRDLS) technique was employed to investigate the changes of the dynamics during gelation process. In both cases, a clear power-law behavior in the time-intensity correlation function, g (2) (τ) -1 ∼ τ n-1 , was observed at the gelation threshold, from which the critical exponent of viscoelasticity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
70
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 22 publications
14
70
1
Order By: Relevance
“…DLS experiments show a remarkably similar behavior of g 2 (t) for very different gel-forming systems such as silica (8,9), Laponite (10), polyurethane (11), polysaccharides (12), PMMA (13), and globular proteins (14). Usually, a fast decay is observed followed by a stretched exponential decay sometimes preceded by power law decay.…”
Section: Introductionmentioning
confidence: 82%
“…DLS experiments show a remarkably similar behavior of g 2 (t) for very different gel-forming systems such as silica (8,9), Laponite (10), polyurethane (11), polysaccharides (12), PMMA (13), and globular proteins (14). Usually, a fast decay is observed followed by a stretched exponential decay sometimes preceded by power law decay.…”
Section: Introductionmentioning
confidence: 82%
“…During the sol-gel transition, the bimode distribution is clearly preserved, although the relative contribution of the fast relaxation decreases. Shibayama and colleagues 145 also reported that the fast mode remained in the formation of silica gels. Another interesting point is that the position of the peak related to the fast relaxation nearly remains during the sol-gel transition, different from other gelling systems.…”
Section: The Slow Mode In Peo-ppo-peo/h 2 O Systemmentioning
confidence: 96%
“…12). vestigated so far: (a) chemical gels, (b) hybrid gels consisting of inorganic silica and organic polymer gels, 96,97 and polymerclay nanocomposite gel, 98 ). It is essential to have (1) an increase in scattering intensity and (2) power-law behavior at gelation threshold, t gel .…”
mentioning
confidence: 99%